French university word list - Ramnäs, Mårten; Lindqvist, Christina (University of Gothenburg, 2026)
The French University word list (FU) is compulsory for first-semester students of French at all Swedish universities. The list has been extracted from the French Nuclear Frequency List (FNFL, Cobb, Lindqvist & Ramnäs, 2026), which is contains the most frequent word families of the French language at large. A word family consists of a head word and its inflected and derived forms. In the FU, certain modifications of the FNFL have been made to suit the targeted learner group. The most important are 1) the FU only contains head word and derived forms, 2) the FU consists of word families that belong to the mid-frequency range, thus excluding the most frequent word families assumed to be already known at the first semester of university studies of French in Sweden, as well as the most low-frequent word families, which are appropriate to study at later stages.

Fransk Universitetsordlista (FU) är obligatorisk för studenter som läser grundkurs i franska (Franska I, Franska A1, Franska allmän kurs) vid alla svenska universitet. Listan har utarbetats från French Nuclear Families List (FNFL, Cobb, Lindqvist & Ramnäs, 2026), som innehåller de vanligaste ordfamiljerna i det franska språket i stort. En ordfamilj består av ett huvudord och dess böjda och avledda former. I FU har vissa ändringar gjorts för att passa den målgrupp som listan riktar sig till. De viktigaste är 1) att FU endast innehåller huvudord och avledda former, 2) att FU består de medelfrekventa ordfamiljerna. Alltså utesluts de mest frekventa ordfamiljerna, som antas redan vara kända vid första terminen av universitetsstudier i franska i Sverige, liksom de mest sällsynta ordfamiljerna, vilka är lämpliga att studera på senare nivåer.
Fransk universitetsordlista
Keywords: Language Technology (Computational Linguistics); french; word list; word families; frequency; lexicon; Natural Language Processing; Språkbehandling och datorlingvistik